Reflection and the stability of belief : essays on Descartes, Hume, and Reid - Loeb, Louis E. (Oxford University Press, 2010)
"This volume brings together twelve of Louis Loeb's articles on modern epistemology. Loeb places Descartes and Hume with Sextus and Peirce in a tradition that adopts psychological properties of belief as the standard for epistemic assessment. Increasingly naturalist investigation of the faculties lead Hume and Reid to reject, and even invert, Descartes' doctrine of reason's superiority to sense-perception"--Back cover